2018
DOI: 10.1101/468801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensembles from ordered and disordered proteins reveal similar structural constraints during evolution

Abstract: Inter-residue contacts determine the structural properties for each conformer in the ensembles describing the native state of proteins. Structural constraints during evolution could then provide biologically relevant information about the conformational ensembles and their relationship with protein function. Here, we studied the proportion of sites evolving under structural constraints in two very different types of ensembles, those coming from ordered or disordered proteins. Using a structurally constrained m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(67 reference statements)
2
2
0
Order By: Relevance
“…The best correlations are found by combining a small (<8) number of conformers rather than the whole ensemble, reflecting distinct contributions of preferred conformations, possibly related to the structure-function relationship of the protein 33,34 . These results agree with previous works describing IDP ensembles as highly redundant 25 and open the opportunity for the development of bioinformatics tools to curate IDPs ensembles databases 35 . Largely ignored in evolutionary studies, except for a few exceptions (for example see [36][37][38] ), contact variations due to .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The best correlations are found by combining a small (<8) number of conformers rather than the whole ensemble, reflecting distinct contributions of preferred conformations, possibly related to the structure-function relationship of the protein 33,34 . These results agree with previous works describing IDP ensembles as highly redundant 25 and open the opportunity for the development of bioinformatics tools to curate IDPs ensembles databases 35 . Largely ignored in evolutionary studies, except for a few exceptions (for example see [36][37][38] ), contact variations due to .…”
Section: Discussionsupporting
confidence: 91%
“…In a previous work we found that IDP ensembles are redundant in terms of their structural constraints on evolution, since ~10 conformers are required on average to explain the structural constraints observed in homologous alignments of IDPs 25 . Following this idea, we explored all possible combinations of different numbers of conformers from each ensemble to study if there is a particular subset of conformers establishing contacts that better explain the evolutionary rate profiles.…”
Section: Effect Of Conformational Ensembles On Evolutionary Ratesmentioning
confidence: 94%
See 1 more Smart Citation
“…The best correlations are found by combining a small (<8) number of conformers rather than the whole ensemble, reflecting distinct contributions of preferred conformations, possibly related to the structure-function relationship of the protein 33,34 . These results agree with previous works describing IDP ensembles as highly redundant 25 and open the opportunity for the development of bioinformatics tools to curate IDPs ensembles databases 35 . Largely ignored in evolutionary studies, except for a few exceptions (for example see [36][37][38] ), contact variations due to conformational changes are revealed as impossible to neglect in IDP ensembles.…”
Section: Discussionsupporting
confidence: 91%